Two women with a man - Unknown:::Creator::::::::::::
Photograph shows a woman looking at a list on a tall table. Another woman standing next to her appears to be either handing out tickets or collecting them. There is a small metal box open on the table and it is facing the women with the ticket. A man with his back to the camera stands across from them.